O exercício aeróbio associado à terapia de contensão induzida modificada em indivíduos hemiparéticos crônicos - Silva, Erika Shirley Moreira (2022)
Introduction: Recovery of upper limb movements in individuals after a stroke is still a challenge. The modified constraint-induced movement therapy (CIMT) presents strong evidence for increasing the use and the recovery of sensorimotor function of the paretic upper limb. Recent studies have also shown that the combination of aerobic exercise (AE) with moderate-high intensity with specific-task training can maximize functional gains. Objectives: To determine the effect of task-oriented training (TOT) priming on upper limb assessments in individuals after chronic stroke. To verify the effect of moderate-high intensity aerobic exercise training in association to CIMT to improve the use and the sensorimotor performance of paretic upper limb in chronic hemiparetic individuals. Methods: PubMed CINAHL, Web of Science, EMBASE, and PEDro databases were searched in October 2019. Outcome data were grouped into measurement categories considering the functional domains of the International Classification (body function and activity). Twenty-five chronic hemiparetic individuals were randomized into two groups: AE + CIMT and Control + CIMT. Feasibility was assessed by eligibility and retention rates, adherence, and satisfaction questionnaire. The occurrence of adverse events was used as a safety criterion. Efficiency measures were evaluated with the primary endpoints: Box and Block Test (BBT), Nine-Hole Peg Test (NHPT), Motor Activity Log (MAL), Wolf Motor Function Test (WMFT), and the secondary endpoint Stroke Specific Quality of Life Scale (SS -QoL). Normality and homogeneity tests and descriptive analysis were applied. A significant level 5% was considered. Thirty-six studies using various types of TOT were included. Stimulation priming showed a significant effect on the Motor Activity Log (quantity: MD 0.50, 95% CI 0.06 to 0.94, P = 0.03 and quality: MD 0.50, 95% CI 0.06 a 0.94, P = 0.03) and upper limb sensorimotor recovery by Fugl-Meyer (MS-FMA) (MD 3.02, 95% CI 0.48 to 5.56, P = 0.02). Regarding sensory priming, significant effects were observed for MS-FMA (MD 4.77, 95% CI 3.25 to 6.29, P < 0.0001) and Action Research Arm Test (MD 7.47, 95% CI 4.52 to 10.42, P<0.0001). For motion priming, significant effects were observed for MS-FMA (MD 8.64, 95% CI 10.85 to 16.43, P < 0.0001). The evidence for action observation priming was inconclusive. Eligibility and adherence rates were 27.1% and 99.2%, respectively. All patients were evaluated at 30-day follow-up, but only 68% returned at 90 days. For the manual dexterity evaluated by the BBT, there was an improvement in all the follow-up. However, we found a minimally significant clinical difference at 90 days in the AEG. Both groups improved the amount and quality of use measured by MAL, WMFT time and FAS. However, it was not observed in the 90 days of AEG for use and in the WMFT time. Quality of life improved throughout the follow-up, with a greater increase for AEG compared to CG. Improvements were maintained at follow-up (day 30). No significant improvement was observed for NHPT, grip strength, and pinch strength. Conclusion: We observed that priming and task-oriented training for upper limb motor recovery in individuals after stroke could be a promising strategy. Movement priming using EA positively affects the brain, cognitive, and health functions, in addition to increasing motor skill learning. Moderate to high-intensity interval AE is a viable and safe option associated with mTCI, with good adherence, leading to improved sensorimotor function. Aerobic exercise as priming should be considered a promising technique to improve motor recovery after stroke.